Chemical and Biological Profiling of Fish and Seaweed Residues to Be Applied for Plant Fertilization - Marios Maroulis; Sevasti Matsia; Georgios Lazopoulos; Oana Cristina Pârvulescu; Violeta Alexandra Ion; Oana-Crina Bujor; Joshua Cabell; Anne-Kristin Løes; Athanasios Salifoglou (Agronomy, 2023)
Brown algae and fish waste contain high-value compounds with potentially beneficial effects on plant growth. Several commercial fertilizer products are currently available, but the characteristics of the materials are usually not well-described. Fish and seaweed residues originating from the Norwegian coast are available, after industrial processing, which may be combined into complete fertilizers exerting additional effects on crop plants (biostimulants). In this study, raw samples of fish and seaweed residues were investigated using ecofriendly technologies (drying, leaching), targeting search and isolation of potential biostimulants, followed by physicochemical characterization (elemental analysis, UV–visible, FT-IR, ICP-MS, ICP-OES, electrical conductivity, pH, etc.). Organic solvent extractions were employed to determine the available mineral content, micro- and macro-nutrients, antioxidant compounds, and amino acid content by chemical hydrolysis. The in vitro biotoxicity profile (cell viability, morphology, migration) of the generated extracts was also perused, employing Gram-positive (Staphylococcus aureus) and Gram-negative bacteria (Escherichia coli) along with sensitive neuronal eukaryotic cell lines N2a58 and SH-SY5Y, to assess their time- and concentration-dependent efficacy as antimicrobials and agents counteracting oxidative stress. The analytical composition of all raw materials showed that they contain important nutrients (K, P, Ca, N) as well as organic compounds and amino acids (Gly, Asp, Glu, Leu, Phe) capable of acting as plant biostimulants. Concurrently, the inherently high conductivity values and salt content necessitated leaching processes, which result in Na+ and K+ decreasing by more than ~60% and justifying further their use in soil treatment formulations. The aforementioned results and assertions, combined with physical measurements (pH, electrical conductivity, etc.) on naturally occurring and dried samples as well as green solvent extracts, formulated a physicochemical profile reflecting well-defined inorganic–organic species that might function as biostimulants. The collective physicochemical and biological properties support the notion that appropriate mixtures of marine organism residues may be efficient fertilizers for crop plants and concurrently possess biostimulant characteristics.